Outcomes after minimally invasive lumbar decompression: a biomechanical comparison of unilateral and bilateral laminotomies - Ho, Yi-Hung (BMC Musculoskelet Disord, 2015)
BACKGROUND: The unilateral approach for bilateral decompression was developed as an alternative to laminectomy. Unilateral laminotomy has been rated technically considerably more demanding and associated with more perioperative complications than bilateral laminotomy. Several studies have indicated that bilateral laminotomy are associated with a substantial benefit in most outcome parameters and thus constituted a promising treatment alternative. However, no complete kinematic data and relative biomechanical analysis for evaluating spinal instability treated with unilateral and bilateral laminotomy are available. Therefore, the purpose of this study was to compare the stability of various decompression methods. METHODS: Ten porcine lumbar spines were biomechanically evaluated regarding their strain and range of motion, and the results were compared following unilateral or bilateral laminotomies and laminectomy. The experimental protocol included flexion and extension in the following procedures: intact, unilateral or bilateral laminotomies (L2–L5), and full laminectomy (L2–L5). The spinal segment kinematics was captured using a motion tracking system, and the strain was measured using a strain gauge. RESULTS: No significant differences were observed during flexion and extension between the unilateral and bilateral laminotomies, whereas laminectomy yielded statistically significant findings. Regarding strain, significant differences were observed between the laminectomy and other groups. These results suggest that laminotomy entails higher spinal stability than laminectomy, with no significant differences between bilateral and unilateral laminotomies. CONCLUSIONS: The laminectomy group exhibited more instability, including the index of the range of motion and strain. However, bilateral laminotomy seems to have led to stability similar to that of unilateral laminotomy according to our short-term follow-up. In addition, performing bilateral laminotomies is easier for surgeons than adopting a unilateral approach for bilateral decompression. The results provide recommendations for surgeons regarding final decision making. Future studies conducting long-term evaluation are required.